Ayurvedic Management of Utthana Vatarakta – A Case Report - Vasanth, Anuja K; Giri, P V; Krishnan, N Navaneeth (International Research Journal of Ayurveda & Yoga, 2024)
A 59-year-old upper-middle-class woman residing in Shornur for the past 10 years and having worked as a nurse for 33 years was admitted to Vaidyaratnam Ayurveda College hospital on September 27, 2023, for a 15-day duration, presenting with complaints of multiple joint pain, left-sided headache, itching of the whole body, crawling sensation persisting for a decade, and blackish discoloration of nails in both upper and lower limbs consistent with nail psoriasis. The diagnosis for this case was established as Utthana Vatarakta, seronegative arthritis. Comprehensive treatment approach involving internal medicines, Rukshana, Snehana, Swedana, Sodhana, and Samana therapies was implemented. Following the 15-day treatment regimen, the patient experienced significant alleviation of complaints improvement in Ama Assessment tool scoring, Visual Analog Scale and Clinical disease activity index.